Evaluation of Formulated Feed for Juvenile Lake Sturgeon Based on Growth Performance and Nutrient Retention. (23rd April 2018) - Lee, Seunghyung; Zhao, Hongxia; Li, Yuquan; Binkowski, Fred P.; Deng, Dong‐Fang; Shepherd, Brian S.; Hung, Silas S. O.; Bai, Sungchul C.
Abstract: This study evaluated the potential of feeding formulated feed to juvenile Lake Sturgeon Acipenser fulvescens and determined the optimal feeding rate of a soft‐moist feed on the growth performance and whole‐body composition of the fish. Six feeding rates (% body weight [BW]/d) of the soft‐moist feed were assigned to each of the 1‐week feeding trials: 2%, 4%, 6%, 8%, 10%, and 12% BW/d for trial I; and 0.5%, 2%, 3.5%, 5%, 6.5%, and 8% BW/d for trial II. As reference diets, frozen bloodworms and a dry formulated feed were administered to the fish at feeding rates of 8% and 5% BW/d for trials I and II, respectively. Each treatment was assigned to three tanks, with either 18 fish (trial I; initial BW [mean ± SD] = 3.5 ± 0.05 g) or 15 fish (trial II; initial BW = 7.8 ± 0.1 g) per tank. No mortality was observed during the two trials. Weight gain and feed conversation ratio were significantly better for fish that received the soft‐moist feed than for those fed the bloodworms. The dry diet and soft‐moist diet resulted in similar growth rates. Growth performance and whole‐body lipid and moisture content were significantly influenced by feeding rates in both trials. The tyrosine, isoleucine, lysine, phenylalanine, and valine levels in whole fish were significantly altered by the feeding rates in trial I, whereas only the glycine level was altered in trial II. Optimum feeding rates based on the specific growth rate were estimated to be 7.6% and 6.2% BW/d (or 1.47 and 1.19 MJ·kg BW −1 ·d −1 ) for Lake Sturgeon weighing 3.5 and 7.8 g, respectively. These results indicate that Lake Sturgeon can be given formulated feed after previous acclimation to the formulated feed during the early life stage.